Análise técnica e econômico-financeira do projeto de um sistema fotovoltaico com geração compartilhada na cidade de Mossoró-RN - Victor, Milla Vitoria Filgueira (Universidade Federal Rural do Semi-Árido, 2020)
This work analyzes the technical and economic-financial feasibility of developing a photovoltaic project with shared generation in the city of Mossoró, state of Rio Grande do Norte, in order to meet the economic demand of 40 consumers medium-sized with monthly consumption of 450kWh. The city in analysis is in constant development and verticalization of urban areas, therefore, a shared generation presents itself as an optimal solution. The solar generation potential in the region was analyzed through meteorological data used in the Radiasol® software, normative resources from the Agência Nacional de Energia Elétrica (ANEEL) and technical data of the equipment chosen in the Brazilian market for the dimensioning of the photovoltaic system. To assess the feasibility of the project's implementation costs, an economic-financial analysis of a return range (TMA = 10%) was expected when returning from the construction of the photovoltaic system. To define the rental price of the system's in m², three different parameters were considered and which were analyzed by economic indicators: TMA (minimum attractiveness rate), NPV (net present value), TIR (internal rate of return), IL (profitability index), payback and ROI (return on investment). A technical analysis about the city of Mossoró revealed that this city presents an excellent generation potential. To meet the consumption profile of these consumer units, a 137.76kWp system was designed, consisting of 336 modules with a power of 410W. A financial analysis showed, in all cases, positive analysis scenarios, but the scenario 1 was chosen because it has more advantages for the investor. For an initial cost of R$ 429,795.30, the rent for the energy shares will be equivalent to a tariff of R $ 0,46/kWh, that means the monthly saving of 30% in electricity costs. The calculated payback was 5 years and 6 months, the ROI was 459,43%. In addition to a profitability index of 3,58 and an IRR of 25,57%. It was concluded, after the requirements of the economic indicators used, that the implementation of the project for a shared generation photovoltaic system in the city of Mossoró, is shown to be quite viable.
Keywords: Energia solar; Geração compartilhada; Análise econômica; Indicadores econômicos; Dimensionamento; Solar energy; Shared generation; Economic analysis; Economic indicators; Dimensioning; ENGENHARIAS::ENGENHARIA ELETRICA